Implementation of the Market Day Program in Fostering Students Entrepreneurship Spirit at Muh Kutowinangun Kebumen Elementary School - Nafissah, Nur Azkiah; Hidayah, Nur (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2024)
This study aims to information regarding the implementation of the market day program in fostering the entrepreneurship spirit of students at SD Muh Kutowinangun Kebumen and to analyze wheter program market day at SD Muh Kutowinangun Kebumen can achieve the goal of growing the soul entrepreneurship the value of independence and communicative value. The benefit of the research is to find out how learning was implementation program market day can foster an entrepreneurial spirit so that it can change students to become more independent and communicative. The research is a phenomenology research using a qualitative descriptive approach. The qualitative this approach is used to describe the implementation of the market day program carried out at Muh Kutowinangun Elementary School, Kebumen. Based on the research results above, it can be concluded that the market day program at Muh Kutowinangun Elementary School, Kebumen, has planning, implementation and evaluation stages and is supported by supporting and inhibiting factors so that it can foster communicative values and independence. The implementation of market day can be said to be successful because upper class students, namely grades 4, 5 and 6, are more communicative and independent than lower class students or students in grades 1, 2 and 3.